Strategy of Fadhlul Fadhlan Pesantren in Developing Media Literacy - Fitri Fitri; Alifa Nur Fitri; Nilnan Ni’mah (The Institute of Research and Service Community IPMAFA Pati, 2022)
The use of internet media in the era of technological and communication advancement is a concern not only in the campus academic community, but in Pesantren, religious-based institutions are also significant. Fadhul Fadhlan is a life skill boarding school (pesantren) that has santri with various levels of education, especially santri as media users who are independently allowed to access online media for educational activities and means of communication. The pandemic demands that the life patterns of santri change, social interaction is limited and cannot be separated from the use of media. Increasingly sophisticated technology supports change and should make it easier for santri to access information, especially in the field of education. Media literacy at Fadhul Fadhlan Pesantren is an interesting study, considering the increasing condition of internet consumption among santri needs to be balanced with smart media skills, so that santri can think more critically in dealing with the flood of information in the media, especially online media.This study focuses on Fadhlul Fadhlan Pesantren strategies to develop media literacy for santri. The results of this study also found that strategies to develop media literacy in Pesantren include optimizing social media, forming media center and training programs to improve literacy skills.